Understanding general and specific associations between cyberbullying and psychopathological symptoms in adolescents: a latent dimensional approach. - Xu, Xiaofeng; Yang, Chi; Huebner, E. Scott; Tian, Lili (European Child & Adolescent Psychiatry, 2024)
Cyberbullying (perpetration and victimization) is a prevalent public health problem associated with a wide variety of psychopathological symptoms (e.g., depression, anxiety, delinquent behaviors, and substance use). However, the generality and specificity of relations between cyberbullying involvement and psychopathological symptoms have not been investigated. Thus, the current study used a latent dimensional approach to examine how cyberbullying (perpetration and victimization) is associated with underlying dimensions of psychopathology as well as with specific symptoms. General and specific associations were estimated by a series of structural equation models with data from 654 Chinese adolescents (52.4% girls, Mage = 12.96 years, SD = 0.67) in a three-wave study. Results indicated that cyberbullying (perpetration and victimization) was significantly and positively associated with latent internalizing and externalizing dimensions. Cyberbullying involvement was non-significantly associated with most specific symptom domains after accounting for the impact of the latent internalizing and externalizing factors. In a few cases, cyberbullying involvement was directly and uniquely associated with specific symptoms. Findings of significant general and symptom-specific associations have important implications for efforts to develop more efficient and targeted strategies for preventing and treating mental health problems associated with cyberbullying.